2023
DOI: 10.1186/s13054-022-04288-3
|View full text |Cite
|
Sign up to set email alerts
|

Using automatic speckle tracking imaging to measure diaphragm excursion and predict the outcome of mechanical ventilation weaning

Abstract: Introduction The speckle tracking ultrasound is an innovative technology enabling distinct assessment of diaphragmatic movement, yet the relative data are scarce. In this pilot study, we sought to evaluate the predictive value of the weaning outcome of automatic speckle tracking in assessing diaphragm excursion. Methods This is a prospective, multicenter, observational study. A total of 160 critically ill subjects underwent speckle-tracking ultrasonography of the right/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Of note, two studies found no association between a low diaphragm TF and extubation failure during tidal breathing but not during SBT [ 5 , 70 ]. The same was reported for DE in another study [ 71 ]. This highlights the importance of evaluating the diaphragm during a challenge test.…”
Section: Impact On Outcomesupporting
confidence: 85%
“…Of note, two studies found no association between a low diaphragm TF and extubation failure during tidal breathing but not during SBT [ 5 , 70 ]. The same was reported for DE in another study [ 71 ]. This highlights the importance of evaluating the diaphragm during a challenge test.…”
Section: Impact On Outcomesupporting
confidence: 85%
“…Hence, a one-dimensional measure is unsuitable to determine absolute values or a safe cutoff for TV. Advanced techniques such as speckle tracking may have superior performance by quantifying diaphragm motion in multiple dimensions [ 15 , 16 ]. Prior studies were often hampered by the application of inspiratory pressure support during ultrasound measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, since we focused on the ultrasound test that was supported by the most evidence of validation at the time of data collection [16, 23-25, 30, 31], a cutaneous marker was not applied to minimize the variability of the ultrasound measurements, as described by Goligher et al [23]. In addition, advanced tools that are used to evaluate diaphragmatic function, such as tissue Doppler and speckle tracking, were not utilized [36][37][38][39].…”
Section: Limitationsmentioning
confidence: 99%